(untitled) (Marketing Journal, 2025)
The article summarizes the countryʼs long -term progress in improving tax administration in the tax sphere, emphasizes the role and importance of the interregional tax inspectorate in improving large -scale reforms aimed at further strengthening the trust of business circles. Some important reforms implemented in the tax system of Uzbekistan have been studied, scientific and practical conclusions and proposals have been developed based on foreign experience and its application in our country. 244